Lightweight And Green Tiles From Recycled Polypropylene Reinforced With Cockle-Shells Powder - Mohamad, Noraiham; Zohid, M. A.; Karim, K. I.; Mazliah, M.; Abd Razak, Jeefferie; Lau, K. T.; Munawar, Rose Farahiyan; Ab Maulod, Hairul Effendy (Universiti Teknikal Malaysia Melaka, 2017)
Fabrication of recycled polypropylene filled with cockle-shells composite tiles via melt compounding and hot pressing method were studied.Cockles-shell powder reinforced polypropylene composites were sieved within particle size range of 63µm – 75µm for different weight ratio of 0 wt%,5 wt%,10 wt%,20 wt%,25 wt% and 30 wt%. Tensile properties was selected as the response.The fracture surface of cockle-hells composite tiles,then were further verified using scanning electron microscopy and fourier transimission infrared radiation.The increasing of cockles-shells powder weight percentage, decrease the tensile strength (14.74MPa to 4.04MPa).In the morphological analysis,limited interaction between fillers and matrices was clearly observed on the fracture surfaces and manifested as voids,cracks,and particles agglomeration also supported by compositional characteristics in term of their their bonding.